Local knowledge of utilization and management of sugar palm (Arenga pinnata) among Cipanggulaan People of Karyamukti, Cianjur (West Java, Indonesia) - RIMBO GUNAWAN; UGA GEMA RAMADHAN; JOHAN ISKANDAR; RUHYAT PARTASASMITA (Biodiversitas Journal of Biological Diversity, 2018)
Gunawan R, Ramadhan UG, Iskandar J, Partasasmita R. 2017. Local knowledge of utilization and management of sugar palm (Arenga pinnata) among Cipanggulaan People of Karyamukti, Cianjur (West Java, Indonesia). Biodiversitas 19: 93-105. Sugar palm, locally known as kawung or aren, (Arenga pinnata (Wurmb.) Merr.) has long been known for its various ecological, economic, and socio-cultural uses among rural people of West Java. Rural people have utilized and managed kawung based on their local knowledge. Nowadays, however, the abundance of kawung trees has been decreasing in many areas, for example, through reduction in planting and destruction. The decreasing experience in managing kawung trees among local people has eroded their local knowledge, and therefore documenting this knowledge is important before it disappears entirely. This paper (i) reports local knowledge of the Cipanggulaan people of Cianjur, West Java on landraces of sugar palm; (ii) identifies various uses of sugar palm by those people, and (iii) describes traditional management systems for the sugar palm conducted by those people. This study adopted qualitative methods developed in ethnobotany based on participant observation and in-depth interviews. Research findings identified two local landraces and at least 10 different plant parts used in various ways. Particular attention was paid to the making of palm sugar in various ways. Conservation of the sugar palm has traditionally been conducted by selective harvesting of the sugar palm fruit and allowing some palms to regenerate naturally.